The aesthetics of brevity. Three classics of the ¨micro story¨: L.M. Díez, J. Mª Merino y J.P. Aparicio¨ (XXI Century. Spanish Literature and Culture, 2007)
In this article, the cultural and historical context into which the ¨micro story¨bursts is expounded upon: a new literary genre sustained in the aesthetic of brevityand the ellipsis, which has reached spectacular development in the Hispanic world.After presenting its distinctive characteristics, the hyper-short stories of three mastersof the genre in Spain are studied: Luis Mateo Díez, José Mª Merino y Juan PedroAparicio.
Keywords: Spanish ¨micro story; aesthetics of brevity and the ellipsis